Peran Mahasiswa KKN UNP dalam Meningkatkan Semangat Kepemudaan melalui Lomba di Jorong Sungai Talang, Nagari Salimpek - Shaiki Roma; Zulsi Febriani; Noriatul Usni; Galuh Atalia; Irfan Rasyid (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The Kuliah Kerja Nyata (KKN) program is a tangible manifestation of higher education's community service. One of the main challenges in rural areas today is the decline in social interaction and the spirit of mutual cooperation among youth due to modernization. This study aims to describe the role of Padang State University KKN students in increasing the enthusiasm and participation of youth in Jorong Sungai Talang, Nagari Salimpek, Lembah Gumanti District. The social intervention carried out was the organization of folk competitions specifically consisting of cracker-eating, eel-catching, chili-grinding, and coconut-grating contests. These competitions were designed to be inclusive for all levels of society, including children, teenagers, mothers, and fathers. This study uses a qualitative approach with the Participatory Action Research (PAR) method. Data collection was carried out through participatory observation, in-depth interviews, and documentation. The results showed that the selection of competition types closely related to the daily life and local wisdom of Minangkabau (such as grinding chilies and grating coconuts) and traditional games (catching eels and eating crackers) was highly effective in breaking social ice. Youth acting as the organizing committee showed a significant increase in enthusiasm and responsibility. Cross-generational participation (from children to parents) created strong social cohesion, revived oral traditions, and fostered communal solidarity in Jorong Sungai Talang.